THE RELATIONSHIP BETWEEN PUBLIC PARTICIPATION IN THE CONSERVATION AND SUSTAINABLE DEVELOPMENT - Kamonnarakitraksa, Thathana; Tovivich, Supitcha (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
This thesis is a descriptive research which explore the relationship between public participation in the conservation and sustainable development. Objective 1.To study the process, levels, and conditions of the public participation in the conservation and the development of the area. 2. To analyze and evaluate the sustainability of the public participation in the conservation and development in various dimensions. And 3. To identify the relations of the public participation in the area’s conservation and development in various dimensions. The three areas are selected to study in this research, including Ampawa Floating Market, Samut Songkram Province, Sam Chuk Old Market, Suphan Buri Province, Klong Suan 100 Year Market, Samut Prakarn Province. The methodology in this research includes a field trip, interview and questionnaire for collecting data from the target group in the social dimension, physical dimension, economic dimension, tourist dimension and the process of public participation. This research aims to evaluate the sustainability and to identify the relations between the process of public participation in the preservation and development of the area in various dimensions which will lead to the formation of approaches to preserve and develop the area sustainably. According to the findings from the analysis of the relations between the sustainability in five dimensions, the conclusion the process of public participation is a factor to promote the sustainability in the social and physical dimensions, but it is not an important factor to promote the sustainability in the economic and tourist dimensions. However, they can be a minor factor to promote the sustainability in the economic and tourist dimensions, because the tourism can bring about advantages and disadvantages to local people and the process of public participation is significant in the sustainable development of local tourism. In addition, the sustainability in an economic aspect relates to the sustainability in the tourist dimension more than the sustainability in other dimensions, because the local tourism is the important variable of the local economy.